Tailoring Management of May-Thurner Syndrome : Case Comparison - Suprapta, Aloysius Yuwono; Kurnianingsih, Novi; Elizabeth Damanik, Gracelia Ruth (Heart Science Journal, 2024)
BACKGROUND: May-Thurner syndrome (MTS) is a post-thrombosis syndrome (PTS) of the lower extremity. This disorder results from compression and/or irritation from adjacent crossing the right common iliac artery to the left iliac venous. In this report, we present two management comparisons of patients with left lower DVT with consideration of MTS.CASE ILLUSTRATION: A 49-year-old male soldier presented with chronic unilateral left leg edema and a mild clinical presentation for 9 months. Previous Doppler ultrasonography (DUS) revealed a thrombus in the left venous femoralis. Anticoagulant was given for six months. DUS and CT venography following anticoagulant treatment revealed a thrombus in the left venous femoralis. Venography revealed entire blockage of the left common femoral and left iliac veins, with adequate collateral flow. PTV was attempted twice and failed both times. The patient was following a conservative therapy (walking exercise and stocking compression) that yielded positive outcomes. A 53-year-old male soldier has had unilateral left leg edema for three years, which has increased during the previous three months with ulceration and active bleeding.Previous Doppler ultrasonography revealed a thrombus in the left iliac externa. Anticoagulants and compression stockings were given for eight months, but the symptoms persisted. CT and venography revealed a complete blockage from the left popliteal vein to the iliac vein. Femoral crossover bypass surgery yielded favorable results.CONCLUSION: Clinically moderate MTS demonstrated fair results with conservative treatment, whereas clinically severe MTS showed superior results with bypass surgery.